Pengaruh Beban Kerja dan Motivasi Kerja terhadap Kinerja Karyawan dengan Gaya Kepemimpinan sebagai Variabel Kontrol - Setiawan, Zhoga; Heriyanto, Heriyanto (Keizai, 2024)
Workload is one of the critical factors in achieving employee performance. A high workload can sometimes make it difficult for employees to perform well, ultimately affecting the company's overall performance. Motivation and leadership style also play a role in employee performance. This study aims to examine the effect of workload and work motivation on employee performance at PT Bisma Dharma Kencana. The population in this study includes harvesting employees and supervisors at the company, with a sample of 95 respondents selected using the convenience sampling technique. Data analysis was conducted using multiple linear regression with SPSS 22. The hypothesis test results show that workload has a partially positive effect on employee performance, as does work motivation, which also has a partially positive effect. A higher workload, accompanied by strong motivation and effective leadership, can lead to better employee performance. Additionally, a high workload is often followed by increased salaries or bonuses, making it reasonable for performance to improve.